Subgingival microbiota and immune response modulation of osseointegrable implants - Nicole Serqueira da SILVA; Ana Carolina Rosa de ALMEIDA; Marvin do NASCIMENTO; Bruno Martins de SOUZA; Talita Gomes Baeta LOURENÇO; Aline Tany POSCH (Faculdade São Leopoldo Mandic, 2023)
ABSTRACT Osseointegrable dental implants are biomaterials made of titanium or other alloys mixed with titanium, which have high biocompatibility and allow osseointegration. However, this process can be modulated by changes in the complex mechanisms between microbiota, immune response and host. The present study aims to present how the immune system-microbiota-host interaction influences the osseointegration process of titanium dental implants and its alloys. A literature review was performed through electronic and manual searches in several databases, including PubMed, LILACS, Google Scholar, SciELO and Web of Science for articles published in the last 20 years in English and Portuguese. The formation of a temporary fibrin matrix on the implants surface after implantation implies the recruitment, adhesion and activity of immune cells at this site, with the release of pro-inflammatory molecules and recruitment of neutrophils. In the second moment, monocytes and macrophages (M1) are recruited, producing, in this step, reactive oxygen species. In the later stage of inflammation, macrophages (M2) help in tissue regeneration with expression of anti-inflammatory cytokines. In addition, the implants surface provides a site for microbial colonization mediated by salivary pellicle and topographical features. Thus, in symbiosis the modulation of the immune response will be favorable to osseointegration. However, the dysbiotic process exacerbates the inflammatory progression modulating the immune response influencing abnormal tissue healing or scar and fibrosis formation, compromising osseointegration. Different conditions of the subgingival microbiota will influence different immunological cascades, generating different cellular responses and positive or negative modulation of the osseointegration process.